Design and Implementation of Microstrip Array Antenna 2x4 Circular Patch with Defected Ground Structure Dumbbell Hexagonal Head 2.4 GHz Frequency for Wi-Fi Application - Tania Izza Sholikhah; Koesmarijanto Koesmarijanto; Hendro Darmono (Jurnal Jaringan Telekomunikasi, 2022)
Wireless technology is a wireless communication technology that is currently widely used by the public to exchange information. The current information exchange is growing as communication requirements rise. The antenna design needs to be improved in order to boost bandwidth. Microstrip antennas are one kind of antenna that can be used for wireless communication. Meanwhile, to improve the bandwidth value of the antenna can be done using the Defected ground structure or DGS technique. The results of testing the microstrip array circular patch antenna with DGS at 2462 MHz frequency show that it has a maximum gain of 15.7 dBi at a frequency of 2530 MHz and a return loss value of -19.3 dB with a VSWR value of 1,242. There is a type of directional radiation pattern in the antenna of the Microstrip Array with DGS. This study's findings indicate that the Circular Array Microstrip antenna with DGS has a bandwidth of 73 MHz while the Circular Microstrip Array without DGS has a lesser bandwidth of 28 MHz.